Clinicopathological Study of Patients Presenting with Adnexal Masses - Asma Batool, Attiya Begum, Sobia Nawaz, Mussarat Sultana, Saima Perveen, Naveed Iqbal, Asma Batool, Attiya Begum, Sobia Nawaz, Mussarat Sultana, Saima Perveen, Naveed Iqbal (Journal of Rawalpindi Medical College, 2019)
Background: To assess the clinicopathological outcome of women with adnexal masses . Method: In this observational study patients with a diagnosis of adnexal mass, who underwent laparotomy, were included. All the patients were evaluated by a complete history, general abdominal and pelvic examination, followed by ultrasonography. Their preoperative findings are then correlated with surgical findings and histopathological diagnosis. Descriptive statistics are applied and results shown in the form of frequencies and percentages. Result: In 50 patients commonest presenting symptom was pain abdomen followed by mass abdomen. Ultrasound features correlate well with histopathological features. Majority (94.6%) patients had benign adnexal pathology and 5.4% had malignant pathology. Most common neoplasms were surface epithelial tumours followed by dermoid cyst. Conclusion:Demographic detail, ultrasonography and CA-125 are good preoperative indicators of malignant nature or benign nature of adnexal masses. Most common adnexal tumours are surface epithelial tumours followed by dermoid cysts and malignant tumours are common in postmenopausal group.